(untitled) (African Journal of Biomedical Research, 2023)
This study assessed the prevalence of and problems of post – bath itching in Ekpoma and it’s environs. It involved the use of questionnaire in obtaining data on the demography, occurrence, duration, perceived cause(s) and intervention strategies in post bath itching. Of the 450 estimated sample size, 400 subjects completely responded to the questions giving a response rate of 88.89%. Overall, 243 of the studied population do experience post bath itching giving a prevalence of 60.75%. The chi-square analysis indicates that males are 3.907 times more likely to experience post-bath itching than females. The duration of itching and the perceived causal factors vary widely among the participant and so are the intervention strategies.